Exploring the Acceptability of Traditional Medicine Clinic Implementation in Indonesian Public Health Centers - Yuniarsih, Sri Mumpuni; Padmawati, Retna Siwi; Madyaningrum, Ema; Mahendradhata, Yodi (Nurse Media Journal of Nursing, 2025)
Background: The World Health Organization (WHO) encourages the integration of traditional medicine (TM) into healthcare services, recognizing its cultural importance in countries like Indonesia. However, this integration needs improvement to ensure quality and accessibility. Previous research has primarily focused on policy implementation or health outcomes with limited exploration of the acceptability of TM clinics in Primary Health Centers (PHCs) from the perspectives of stakeholders using the Theoretical Framework of Acceptability (TFA). Operational and ethical challenges of this integration remain underexplored.Purpose: The purpose of this study was to explore the acceptability of traditional medicine clinics in PHC settings using the TFA, focusing on the perspectives of healthcare workers, traditional medicine practitioners, and patients.Methods: An exploratory qualitative study was conducted in five PHCs in Boyolali, Indonesia, with 25 participants, including healthcare workers, traditional medicine practitioners, and patients. Participants were purposely selected based on the following inclusion criteria: (1) healthcare workers providing services in traditional medicine clinics at PHCs, (2) traditional medicine practitioners operating within the clinic area, and (3) patients who had used the clinic’s services at least once. Data were collected through in-depth interviews and analyzed using a thematic approach.Results: Thematic analysis identified four key themes: (1) Perceived Benefits and Trust in TM Clinics, with participants reporting high satisfaction and trust in the services, (2) Readiness and Competency of Healthcare Workers, emphasizing confidence, ongoing training, and collaboration with traditional medicine practitioners, (3) Barriers to Acceptability and Implementation, including heavy workloads, limited resources, and a lack of dedicated personnel, and (4) Alignment with Professional and Cultural Values, focusing on the importance of cultural integration and ethical considerations for the sustainability of TM clinics.Conclusion: Traditional medicine clinics in PHCs are generally well accepted, but their sustainability depends on addressing resource constraints and enhancing staff training. Strategic investment and policy support are crucial for overcoming operational and ethical challenges and ensuring the successful integration of public health services.